The Issue Of Greek And Syriac Influence On The Emergence Of The Science Of Nahw - Muhammed Mahmut Olçun (Kocatepe İslami İlimler Dergisi)
Before the science of grammar became a systematic branch of science in the Arabic language, the foundations of this science began to be laid. In order to protect the Arabic language from linguistic errors and most importantly to read and understand the Holy Qur'an correctly, Arabic language grammar studies started in the Sadr al-Islamic period. In the following periods, these studies began to be put forward systematically and grammatical schools emerged. With the Basra school of grammar, which was the first school of grammar to emerge, grammar studies became systematized. Important studies on Arabic grammar in Basra led to the development of this science and its spread to different cities. The language scholars trained in Basra were instrumental in the birth of the madrasas of Kūfah and Baghdad in the Eastern Arab world and the Andalusian grammar school in the Western Arab world. These grammatical schools, which carried out studies on the science of grammar, endeavored to determine the rules of language by following different paths. There are some claims put forward by some western orientalists about these studies that started in the early periods of Islam. These orientalists claim that Syriac and Greek grammars were influential on the birth of Arabic grammatical studies. There are also observers who disagree with and oppose the orientalists who put forward this claim. Scholars in the Arab world and in our country have written various studies on this issue raised by Western Orientalists. The most important feature of our study, which distinguishes it from other previous studies on this subject, is that it evaluates the issue in the context of istishhād from the verses, hadīths and Arabic poetry, which are extremely important in determining the rules of grammar. This is because witnessing from classical Arabic poetry and verses is of great importance in determining the rules of grammar. The data we have obtained in this study are extracted and presented using the interpretive research technique and qualitative research technique.